Medical tests sourcebook : basic consumer health information about preventive care guidelines, routine health screenings, home-use tests, blood, stool, and urine tests, genetic testing, biopsies, endoscopic exams, and imaging tests, such as X-ray, ultrasound, computed tomography (CT), and nuclear and magnetic resonance imaging (MRI) exams; along with facts about diagnostic tests for allergies, cancer, diabetes, heart and lung disease, infertility, osteoporosis, sleep problems, and other specific conditions, a glossary of related terms, and directories of additional resources - Omnigraphics, Inc. (Detroit, MI: Omnigraphics, 2018)
"Provides basic consumer health information about endoscopic, imaging, laboratory, and other types of medical testing for disease diagnosis and monitoring, along with guidelines for screening and preventive care testing in children and adults. Includes index, glossary of related terms, online access, and other resources"--
Includes bibliographical references and index.
Keywords: Diagnosis -- Popular works; Diagnosis, Laboratory -- Popular works; Medicine, Popular